THU0457 Interleukin-6 expression in inflamed and non-inflamed temporal arteries from patients with giant cell arteritis. (12th June 2018) - Pipitone, N.; Muratore, F.; Tamagnini, I.; Cavazza, A.; Cimino, L.; Boiardi, L.; Restuccia, G.; Bonacini, M.; Croci, S.; Salvarani, C.
Abstract : Objectives: To evaluate if interleukin-6 (IL-6) expression in the temporal artery biopsy (TAB) specimens may differentiate patients with giant cell arteritis (GCA) from those without. Methods: 63 consecutive formalin-fixed, paraffin-embedded (FFPE) TABs performed between 2009 and 2012 from 32 patients with transmural biopsy-proven GCA, 8 patients with biopsy-negative GCA and 23 controls were retrieved. Demographic, clinical, and laboratory data at presentation and at each follow-up visit were collected. A pathologist reviewed all TABs. Immunohistochemistry was performed on 4 µm FFPE tissue sections with a 1:400 dilution of rabbit polyclonal anti-human IL-6 antibody (NOVUS Biologicals Littleton, Co.) for 60' at 37°. Slides of TAB specimens were independently assessed by five readers. IL-6 expression was graded as 0 (absent), 1 (mild), 2 (moderate) and 3 (marked). Inter-reader differences were resolved by consensus. Anti-IL6 staining was considered positive if staining was grade 2 or 3, since grade 1 was faint, sometimes difficult to differentiate from background, and showed the least degree of agreement between readers. Results: TAB specimens from patients with biopsy-proven GCA, biopsy-negative GCA and controls were positive for anti-IL-6 staining in 59%, 13% and 48% of cases, respectively, the difference between biopsy-proven and biopsy-negative GCA patients being significant (p=0.04). In non-inflamed TABs, IL-6 was mainly expressed by mesenchymal cells in media and intima layers, while in inflamed TABs IL-6 was mainly expressed by mononuclear inflammatory infiltrating cells. IL-6 grade 2–3 expression was observed in all 6 patients with visual loss compared to 25 (43.9%) of 57 patients without (p=0.011). Blindness was recorded in 2 patients with biopsy-proven GCA and 4 controls (all with a final diagnosis of non-arteritic ischaemic optic neuropathy). No associations were found between IL-6 expression and demographic characteristics, GCA signs/symptoms, laboratory and histopathological TAB findings. However, there was a statistical trend (p=0.055) of increased frequency of the halo sign at temporal artery CDS in patients with IL-6 expression grade 2–3 compared to those with IL-6 expression grade 0–1. No significant differences for the expression of IL-6 were observed between patients with and without PMR (5/8%–62.5% - versus 6/15%–40% -, p=0.400) and between patients with isolated PMR and those with TAB positive GCA (62.5% vs 59%, p=1.000). Conclusions: Our study provides evidence that IL-6 expression does not increase the sensitivity of TAB in patients with morphologically uninflamed arteries. A search for further markers that may increase the sensitivity of TAB is warranted. Disclosure of Interest: None declared